ANALISIS DISIPLIN KERJA, KOMPETENSI, DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI DENGAN MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING DI KANTOR PELABUHAN KOTA BATAM PROVINSI KEPRI - Siagian, Mauli (EDUTECH CONSULTANT, 2017)
This study aims to determine empirically the effect of labor discipline, competence, and communication to employee performance with work motivation as an intervening variable in the Office of the Port of Batam. This study uses 117 respondents as samples. Data were analyzed by using path analysis with the help of statistical software SPSS 21. The results of this study are: the discipline of work has a significant direct effect on work motivation at the Port Office Batam Riau Islands Province, competencies have a significant direct effect on work motivation in the Office port Batam Riau Islands province, communication has a direct impact significantly on work motivation at the port Office Batam Riau Islands Province, the discipline of work has a direct impact significantly on the performance of employees in the Office of the port of Batam Riau Islands Province, competency has a direct impact significantly on employee performance the Port Office Batam Riau Islands Province, communications have a significant direct effect on the performance of employees in the Office of the Port of Batam Riau Islands province, motivation has a significant direct effect on the performance of employees in the Office of Pel Abuhan Batam Riau Islands province, work discipline not significant effect on the performance of employees through employee motivation, competence not significant effect on the performance of employees through employee motivation, communication significant effect on the performance of employees through workmotivation.